A Study on the Role of Selected Hr Practices and Hr System In Affecting the Performance of the Companies: Navigating the Evolving Business Landscape (Journal of Advances and Scholarly Researches in Allied Education, 2013)
A turbulent business environment, highly demandingcustomers, formidable competitors, technological innovations, shorteningproduct life cycles and low barriers to entry, have forced organizations to puta higher emphasis on learning. Organizations are becoming more fluid,facilitating networks of customers, suppliers and business partners. Boundariesof organizations are becoming blurred and departmental barriers are fading.Corporations are becoming flatter and leaner. Empowerment is replacing powerand revolutionary change is swapping with incremental change. The companies nowhave to find and retain their positions not only in local or national marketbut also have to explore markets worldwide. To survive, prosper and succeed incurrent business environment, the organizations have to be proactive instead ofbeing reactive. The need of the hour is to think the unthinkable, try whatseems to be impossible, put your best to bring forth novel ideas and thenimplement them to revolutionize the world.